Analisis Efisiensi Teknis Usahatani Durian Bawor di Kecamatan Kemranjen Kabupaten Banyumas - Pratama, Muhammad Faza; Mulyani, Altri; Setiawati, Indah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study focuses on the decline in durian production in Kemranjen subdistrict in 2021 and 2022. Bawor durian is a type of durian that is widely cultivated by farmers in Kemranjen subdistrict. The objectives of this study are: 1. To identify the factors influencing the production of Bawor durian farming 2. To determine the technical efficiency level of Bawor durian farming production 3. To identify the factors influencing the inefficiency of Bawor durian farming. The study was conducted in Alasmalang Village, Karangsalam Village, and Pageralang Village in Kemranjen Subdistrict, Banyumas Regency. Sampling was conducted using the census method. The sample size for this study was 62 farmers. The analysis method used stochastic frontier analysis. The results of the study indicate that the production factors significantly influencing durian bawor production are manure, NPK fertilizer, dolomite, pesticides, and the number of trees. The average technical efficiency value of Bawor durian farming is 0.71738845. The factors significantly influencing the inefficiency of Bawor durian farming are age and extension services. The results of this study are useful as a guideline for Bawor durian farmers in Kemranjen Subdistrict to achieve maximum results.